Method for determining integral indicators quality of life for - Рыбак, Анатолий Иванович; Панафидин, Геннадий Сергеевич (Technology audit and production reserves, 2014)
This article provides an analysis of the quality of life, which is determined by the vital potential of society, social groups and individuals, and compliance characteristics of processes, tools, conditions and results of their positive social life needs, values and objectives. For valuation used the following methods: rating method, the method of linear scaling, the method of scoring, the method of assessing the quality of life of the population of the region relative to the group of regions. The variants of aggregate indicators of quality of life, reflecting certain qualitative properties of the system . Quality of life is based on the following principles: a comprehensive assessment; comprehensiveness and universality of the principle of the specificity of the research object. Based on the analysis of quality of life assessment models, proposed an integral indicator of the quality of life, including the following criteria: quality of the population, welfare, social security and environmental quality.